A influência das restrições financeiras na gestão tributária das empresas brasileiras - Danielle Penido Teixeira (2018)
The questions about tax collection in Brazil are increasingly debated in society, mainly because it is almost unanimous that the current level of taxation is excessive. A growing front of studies has focused on analyzing the determinants of tax management. Thus, the researchers seek to identify the characteristics of companies potentially associated with activities related to this practice, including the level of indebtedness, capital intensity, inventory intensity, levels of corporate governance, independence of the board of directors among others. In this study, the impact of financial constraints on the tax management behavior of a company is verified. It is interesting to note that in a situation of financial constraint, traditional financing sources become more expensive or less accessible and companies seek alternatives to fund their operations. In this case, tax management can be viewed as a potential source of resources to the extent that it reduces reported taxable profit or increases tax credits, thereby reducing tax collection. The general objective of this research was to verify the relationship between financial constraints and the adoption of tax management practices of Brazilian companies. For this purpose, tax management was identified in Brazilian non-financial companies in the period from 2012 to 2016 by calculating the CashETR proxy, which refers to the percentage measure between tax expenses and accounting profit for three years. As a preliminary result, it was verified that Brazilian companies adopt tax management practices, since CashETR had effective tax rates of 23.2%, or approximately 11 percentage points lower than the main nominal rate (34%) of taxes on the current profit in the analyzed period (2012 - 2016). In addition, it was identified that the year 2015 had the lowest effective rate (CashETR = 21.7%), which may have been due to the economic stagnation observed in this period and the consequent retraction of economic activity in the Brazil (IBGE, 2015). Identifying the tax management and using the statistical approach of panel data, we related the calculated proxies to the characteristics of financial constraint: (i) size, (ii) payment of dividends and repurchase of shares, (iii) financial leverage, (iv ) issuance of ADRs and (v) classification of credit risk. As a result, it was found that the payment of dividends, the effective repurchase of shares, the issuance of ADRs and speculative grade ratings, which were expected to be positively related to the CashETR proxy, showed the expected sign in the regression and were significant at the 5% level. This result indicates, therefore, that companies with financial restraint characteristics are engaged in the adoption of tax management practices that reduce their taxable profit and, consequently, their effective tax rate. Finally, statistical significance was verified in the control variables used in the model, demonstrating that profitability (ROA), corporate governance segment and crisis are characteristics that influence the tax management calculated by CashETR.